Modelling, computation and optimization in information systems and management sciences Second International Conference MCO 2008, Metz, France - Luxembourg, September 8-10, 2008, Proceedings - MCO 2008 (Communications in computer and information science, 2008)
This book constitutes the refereed proceedings of the Second International Conference MCO 2008, Metz, France, September 2008. The 65 revised full papers presented were carefully reviewed and selected from 160 submissions. The papers are organized in topical sections on optimization and decision making; data mining theory, systems and applications; computer vision and image processing; computer communications and networks; optimization and search techniques for security, reliability, trust. MCO 2008 -- Optimal flight paths reducing the aircraft noise during landing -- Scalability analysis of a novel integer programming model to deal with energy consumption in heterogeneous wireless sensor networks -- Single straddle carrier routing problem in port container terminals: mathematical model and solving approaches -- Employing “Particle Swarm Optimization” and “Fuzzy Ranking Functions” for direct solution of EOQ problem -- Linear reformulations of integer quadratic programs -- Control of some graph invariants in dynamic routing -- A simulation tool for analyzing and improving the maternity block management -- Solving the multiple objective integer linear programming problem -- Generalized polychotomic encoding: a very short bit-vector encoding of tree hierarchies -- Mathematical programming formulations for the bottleneck hyperplane clustering problem -- Constraint propagation with tabu list for min-span frequency assignment problem -- Evolutionary optimisation of kernel and hyper-parameters for SVM -- Lot-sizing and sequencing on a single imperfect machine -- Best and worst optimum for linear programs with interval right hand sides -- Transit network re-timetabling and vehicle scheduling -- Traveling salesman problem and membership in pedigree polytope - a numerical illustration -- The minimum weight in-tree cover problem -- On importance of a special sorting in the maximum-weight clique algorithm based on colour classes -- An extended comparison of the best known algorithms for finding the unweighted maximum clique -- An adapted branch and bound algorithm for approximating real root of a ploynomial -- Portfolio selection under piecewise affine transaction costs: an integer quadratic formulation -- An exact method for a discrete quadratic fractional maximum problem -- Disaggregation of bipolar-valued outranking relations -- A performance study of task scheduling heuristics in HC environment -- Performance evaluation in a queueing system M2/G/1 -- Outcome-space polyblock approximation algorithm for optimizing over efficient sets -- A DC programming approach for mixed-integer linear programs -- Simulation-based optimization for steel stacking -- Robust hedging of electricity retail portfolios with CVaR constraints -- Value functions and transversality conditions for infinite horizon optimal control problems -- Modeling the mobile oil recovery problem as a multiobjective vehicle routing problem -- Empirical analysis of an online algorithm for multiple trading problems -- A novel approach for the nurse scheduling problem -- Postoptimal analysis in nonserial dynamic programming -- A novel optimization in guillotine cut applied reel of steel -- Robust production planning: an alternative to scenario-based optimization models -- Challenging the incomparability problem: an approach methodology based on ZAPROS -- DC programming approach for a class of nonconvex programs involving l 0 Norm -- Finding maximum common connected subgraphs using clique detection or constraint satisfaction algorithms -- Analysis and solution developement of the single-vehicle inventory routing problem -- A methodology for the automatic regulation of intersections in real time using soft-computing techniques -- Composite dispatching rule generation through data mining in a simulated job shop -- Co-author network analysis in DBLP: classifying personal names -- On clustering the criteria in an outranking based decision aid approach -- A fast parallel SVM algorithm for massive classification tasks -- A wavelet based multi scale VaR model for agricultural market -- Using formal concept analysis for the extraction of groups of co-expressed genes -- Join on closure systems using direct implicational basis representation -- G 1 blending B-spline surfaces and optimization -- A delineation algorithm for particle images online -- Improving inter-cluster broadcasting in Ad Hoc networks delayed flooding -- Improved time complexities of for the directional minimum energy broadcast problem -- Optimised recovery with a coordinated checkpoint/rollback protocol for domain decomposition applications -- A context-aware broadcast protocol for mobile wireless networks -- Stability of two-stage queues with blocking -- A competitive neural network for intrusion detection systems -- Transfer graph approach for multimodal transport problems -- Wireless traffic service communication platform for cars -- System architecture for C2C communications based on mobile WiMAX -- Accuracy and efficiency in simulating VANETs -- Design of highly nonlinear balanced boolean functions using an hybridation of DCA and simulated annealing algorithm -- Non-standard attacks against cryptographic protocols, with an example over a simplified mutual authentication protocol -- Provable security against impossible differential cryptanalysis application to CS-cipher -- VNSOptClust: a variable neighborhood search based approach for unsupervised anomaly detection.